Refining the planktic foraminiferal I/Ca proxy: results from the Southeast Atlantic Ocean - Lu, W; Dickson, AJ; Thomas, E; Rickaby, REM; Chapman, P; Lu, Z (Elsevier, 2019)
Profound changes in upper ocean oxygenation have taken place in recent decades and are expected to continue in the future, but the complexity of the processes driving these changes has yet to be fully unraveled. Planktic foraminiferal I/Ca is a promising tool to reconstruct the extent of past upper ocean oxygenation, but a thorough assessment is necessary to evaluate both its potential and its limitations. We used foraminifers from Holocene core-tops (Southeast Atlantic Ocean) to document planktic I/Ca across a range of oceanographic conditions. Subsurface O2 concentrations may be the dominant control on planktic foraminiferal I/Ca and planktic I/Ca decreases rapidly at low O2 conditions (O2 < ∼70–100 µmol/kg). We thus document that low planktic I/Ca can be used empirically to indicate hypoxia in the upper water column, but questions remain as to the mechanistic understanding of the relation between seawater iodine speciation change, its O2 threshold and foraminiferal I/Ca. Planktic I/Ca records from core GeoB1720-2 (Benguela Upwelling System, SE Atlantic) suggest that hypoxic waters were present near the site persistently during the last 240 ka, without clear glacial-interglacial variability.